Comprehensive review on patulin and Alternaria toxins in fruit and derived products - Bacha, Syed Asim Shah; Li, Yinping; Nie, Jiyun; Xu, Guofeng; Han, Lingxi; Farooq, Saqib (Frontiers in Plant Science, 2023)
Fungi play a considerable role in the spoilage of fruits because of their pathogenicity to the harvested products. During the various phases of pathogenesis, some of these fungi may generate different mycotoxins and secondary metabolites that are toxic to humans and animals that consume the products. During the last century, various fruits that form part of our daily diet have been added to the products exposed to mycotoxin contamination. Some of these mycotoxins are carcinogenic, and most of them are highly stable during processing and, therefore, can reach the consumer. Patulin is a mycotoxin characteristic of infected fruits. Although Penicillium expansum is the primary pathogen responsible for patulin production in apples, pears, and various stone fruits, other Penicillium species involved in fruit decay may produce a variety of mycotoxins during their life cycle in the host. Alternaria mycotoxins, including alternariol, alternariol methyl ether, altenuen, tenuazonic acid, and altertoxins, may be produced naturally in a wide range of fruits under both cold-storage and shelf-life conditions. Although A. alternata has been considered the major mycotoxin-producing species, other members of the genus, such as A. citri, A. solani, A. longipes, and the A. tenuissima, A. arborescens, and A. infectoria species groups, are also capable of producing these toxic contaminants in their hosts. The present review deals with the significant mycotoxigenic fungi that attack harvested fruits, i.e., Aspergillus, Penicillium, and Alternaria species, and the mycotoxins produced in the host tissues, e.g., patulin and Alternaria toxins. Further, this review brings together, for the first time, subjects relevant to mycotoxin production, accumulation, natural occurrence importance in fruit and derived products, and ways for their detection methods.